Pertumbuhan dan Hasil Kacang Hijau dari Berbagai Populasi dengan Mulsa Organik - Amalia Dita Riyaningsih; Supriyono Supriyono; Jauhari Syamsiyah (Agrotechnology Research Journal, 2018)
Mung beans are one of the common beans comodities consumed after soybeans and peanuts. The national mung beans production was 0.7 tons in average, which is lower than the potential yield. Production of mung bean can be improved by modifying the microclimate by mulching and regulating crop density. The purpose of this research was to improve the yield of mungbean. Research method used was Completely Randomized Design (CRD). The treatments were organic mulching of mahagony leaves, straws, husks, and without mulch (M1, M2, M3, M0) and the crops density 1 and 2 crops (B1 and B2). The results showed interaction between organic mulches and crops density significantly affected the crops’ height and number of productive branches. Interaction of straw mulches and two crops density increased the crops’ height 37,91% than the control and has the most productive branches. Organic mulches significantly affected to flowering period and number of hardseeds. Husk mulches accelerated flowering period and decrease the number of hardseeds. Organic mulch and number of crop’s density treatments has not to improve the yield of mungbean yet. The yield of mungbean can achieved in this research was 1,54 ton ha-1.